Defining success in business retention and expansion: What do economic development organizations measure and why?. Issue 2 (15th March 2017) - Morgan, Jonathan Q.; Morphis, Crystal
Abstract: Understanding what constitutes success in business retention and expansion (BRE) is a vital first step in determining the extent to which economic development organizations (EDOs) emphasize and use performance measurement for this particular strategy. The limited literature available on the topic suggests that the emphasis EDOs place on performance measurement in BRE will vary, and is likely a function of certain organizational and program characteristics. As such, the article seeks to address three inter-related research questions: (1) How do EDOs define success in BRE based on the specific metrics they collect? (2) What factors explain the variation in emphasis that EDOs place on BRE metrics? and (3) What success factors are evident in the implementation of BRE programs that may increase the chances of achieving desired results? The analysis uses data from a national survey of EDOs and short case studies of five BRE programs in examining the research questions.